Cross-Sectional Analysis of Factors Predicting Food Assistance Stigma - Frances Hardin-Fanning; Ratchneewan Ross; Shuying Sha (Behavioral Sciences)
The stigma associated with food assistance can be a barrier to resolving food insecurity. Self-reliance expectations likely contribute to this stigma. Aim: This cross-sectional study identified factors that predict perceptions of food assistance stigma. Demographics (age, sex, race, and ethnicity) were collected, and food assistance stigma (Food Resource Acceptability) and self-reliance (Self-Reliance Scale) were measured via REDCap questionnaires from 531 online participants. The research volunteer repository, Research Match, was used for recruitment. Multiple regression was conducted to determine food assistance stigma predictors. Older age, being male, and reporting higher self-reliance significantly predicted the likelihood of stigmatizing food assistance. The social expectation of self-reliance in adulthood contributes to an assigned and anticipated stigma associated with accepting food assistance. This stigma permeates many regions, particularly the United States, and likely contributes to unresolved food insecurity despite the availability of multiple food assistance resources. Future qualitative research should be conducted among older individuals and males with high levels of self-reliance to gain a deeper understanding of how food assistance stigma could be lessened so that appropriate stigma reduction interventions could be tested among this target group.